96 Safety and effectiveness of outpatient based acute heart failure care: a randomised controlled feasibility trial. (17th July 2020) - Wong, Kenneth; Latt, Nang Khaing Zar; Debski, Maciej; Abdelrahman, Amr; Taylor, Rebecca; Wong, Suzanne; Cassidy, Christopher; Seed, Alison; Galasko, Gavin; Wilson, David; Davis, Gershan; Lang, Chim; et al.
Abstract : Introduction: Worsening heart failure (HF) leading to hospital admission is common and associated with substantial morbidity and mortality. For many patients, the preferred place of care, including end-of-life care, is at home or in the community, but this is often thwarted by the need for intravenous (IV) diuretic therapy. Alternative models of ambulatory care exist but safety and efficacy should be compared to standard care in randomised controlled trials (RCT). Methods: We randomised patients with pulmonary or peripheral oedema who no longer required supplementary oxygen and who were considered to need at least two more days of IV diuretic treatment. A left ventricular ejection fraction <50% by any imaging modality and /or right ventricular impairment and documentation of a plasma brain natriuretic peptide (BNP) >100pg/mL within the previous two years were also required. Patients who were admitted to hospital as well as those seen in the emergency department or out-patient clinic could be enrolled. Patients were randomised to be admitted (conventional care) or for out-patient care (at home, in the community centre, or in a hospital 'Furosemide lounge'. The primary safety outcome was all-cause mortality during the index episode and primary effectiveness outcome was the number of full days alive and out of hospital (which did not include day-care in the Furosemide lounge) within 30 days after randomisation. Statistical analysis was based on 'intention to treat'. Results: Of 24 patients enrolled, eleven were randomised to in-patient and thirteen to out-patient care. There was no statistically significant difference in all-cause mortality. Only one patient, who was randomised to inpatient care, died. Patients randomised to in-patient care accrued 16 [IQR 12.5 to 20.5] days alive out of hospital compared to 29 [IQR 20.5 to 29] days for those assigned to out-patient care (p=0.015). Two patients randomised to in-patient care required readmission within 30-days compared to five assigned to out-patient care. Using these data, we calculate that a trial using this primary endpoint would require 92 patients to show, compared to standard in-patient care, that outpatient care leads to at least two more days alive and out of hospital with 90% power. Conclusion: In this feasibility RCT, out-patient intravenous diuretic treatment was associated with a favourable outcome compared to standard inpatient care which might also be a cost-effective and an approach to care preferred by many patients. Conflict of Interest: No conflict of interest